Pengunaan Sufiks Pernyataan Biaya è³ƒã€ é‡‘ dan ï½žè²» dalam Mainichi Shinbun dan Minami Nihon Shinbun - Tjokrokusumo, Kezia Angelica; Fatonah, Siti; Alfiani, Khori; Wulan, Ardhini Wahyu (Universitas Airlangga, 2024)
This study aims to investigate the derived features of the suffixes -chin (賃), -kin (金), and -hi (費) in the corpus of Mainichi Shinbun and Minami Nihon Shinbun electronic newspapers over nearly one year. Within more than 20,000 sentences containing these three suffixes, this study reveals the important role of terms related to cost, funds, and expenses in Japanese public discourse. The analysis was conducted to understand the context in which each suffix used, identify its usage pattern, and distinguish its specific meaning. The results show that -chin (賃) suffix is often used for service fees or rent, -kin (金) suffix relates to funds or money in formal contexts, while -hi (費) suffix refers to expenses or costs in general contexts. The results also highlight the sensitivity of language to economic and social issues, while providing in-depth insights into the construction of Japanese in mass media. This research contributes to studying Japanese linguistics, particularly in understanding the function of suffixes in word formation and information delivery in the public sphere.